2020
DOI: 10.3390/foods9081108
|View full text |Cite
|
Sign up to set email alerts
|

Legacy and Emerging Contaminants in Demersal Fish Species from Southern Norway and Implications for Food Safety

Abstract: The present study aimed at measuring the levels of legacy and emerging contaminants in fillet samples from four demersal fish caught in two fishing sites from Southern Norway, in order to assess possible implications for food safety. Levels of organochlorine compounds (OCs), organophosphate pesticides (OPs), polychlorinated biphenyls (PCBs), polybromodiphenyl ethers (PBDE), per- and polyfluoroalkyl substances (PFASs), and polycyclic aromatic hydrocarbons (PAHs) were measured in fillet from Atlantic cod (Gadus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Being demersal fish species, Pleuronoectiformes and Rajiformes are more likely to accumulate PCBs and hazardous trace elements than other fish species ( 13 ). Therefore, when frequently eating flatfish or ray, the matter of food safety must be considered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being demersal fish species, Pleuronoectiformes and Rajiformes are more likely to accumulate PCBs and hazardous trace elements than other fish species ( 13 ). Therefore, when frequently eating flatfish or ray, the matter of food safety must be considered.…”
Section: Resultsmentioning
confidence: 99%
“…High methylmercury exposure in pregnant women directly affects the neurodevelopment of the fetus ( 12 ). Moreover, bioaccumulation of persistent organic pollutants such as, e.g., polychlorinated biphenyls (PCBs) can pose serious health issues due to their persistence and toxicity to the human body ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…To tackle for the contamination and to prevent potential risks for ecosystem and human health, in August 2018 a series of restoration activities, including the dredging of bottom sediments and the covering of the seabed with sand to isolate any residual of contamination, were implemented. Previous studies on mussels (Parolini et al, 2020a ) and demersal fish (Parolini et al, 2020b ) showed an increase in organohalogen compounds after the beginning of restoration activities, with potential human health risk due to mussel consumption (Parolini et al, 2020a ). As to date no information is available for TEs, the main goals of this study were the monitoring of TEs levels and trends before and during the sediment restoration activities, as well as the assessment of potential health risk due to human consumption of contaminated mussels.…”
Section: Introductionmentioning
confidence: 96%
“…Polychlorinated biphenyls (PCBs) are persistent organic pollutants (POPs) which have been described as organohalogenic and legacy/traditional contaminant [1]- [2] and are known to be environmental endocrine-disrupting chemicals [3]- [5]. All PCBs are synthetic and hydrophobic organic chemicals (HOCs) that still abound in sediment and in wildlife including fish [6].…”
Section: Introductionmentioning
confidence: 99%